Inhibition of Glycogen Synthase Kinase and the Neuroprotective Function of Conjugated ZnO-Osthol Nanoparticles in Alzheimer’s Disease - Nahed S. Alharthi; Fahad M. Aldakheel; Abdulkarim S. Binshaya (Bioinorganic Chemistry and Applications)
A critical factor in the cause and progression of Alzheimer’s disease (AD) is the growth of β-amyloid peptide (Aβ) in the brain. The mechanism of this effect is still unknown, although the effect of osthol on Aβ-induced inflammation is neuroprotective in AD and supplementation with zinc might prevent or delay the onset of dementia. In the current study, by inducing APP vector in human BE (2)-M17 cells, we established a cellular model of AD and investigated the protective effect of osthol (7-methoxy-8-3-methyl-2-butenyl-2H-1-benzopyran-2-one)-zinc oxide nanoparticles. The osthol-conjugated zinc oxide nanoparticles could significantly increase cell viability by inhibiting cell apoptosis. Osthol treatment has also prevented synaptic proteins such as postsynaptic density-95 (PSD-95), synaptophysin (SYP), and synapsin-1 from decreasing in APP-induced BE (2)-M17 cells. In addition, the expression of miR-132 was significantly upregulated by osthol by triggering the Wnt/β-catenin signaling pathway. We conclude from our observations that osthol is a potential drug for the treatment of a neurodegenerative disease, Alzheimer’s. The key reason was that by upregulating miR-132, osthol could inhibit APP expression to prevent AD from occurring.